One-Pot Synthesis of N-Substituted β-Amino Alcohols from Aldehydes and Isocyanides - Cioc, Răzvan C.; van der Niet, Daan J. H.; Janssen, Elwin; Ruijter, Eelco; Orru, Romano V. A. (Chemistry : a European journal, 2015)
A practical two‐stage one‐pot synthesis of N‐substituted β‐amino alcohols using aldehydes and isocyanides as starting materials has been developed. This method features mild reaction conditions, broad scope, and general tolerance of functional groups. Based on a less common central carbon–carbon bond disconnection, this protocol complements traditional approaches that involve amines and various carbon electrophiles (epoxides, α‐halo ketones, β‐halohydrins). Medicinally relevant products can be prepared in a concise and efficient way from simple building blocks, as demonstrated in the synthesis of the antiasthma drug salbutamol. Upgrading the synthesis to an enantioselective variant is also feasible. Retrosynthesis revisited: A practical and general two‐stage one‐pot synthesis of N‐substituted β‐amino alcohols using aldehydes and isocyanides as starting inputs is described (see scheme). Medicinally relevant compounds can be prepared in a concise and efficient way from simple building blocks, as demonstrated by the synthesis of the antiasthmatic drug salbutamol. The reaction can readily be made asymmetric by using a chiral Lewis base catalyst.